Comparison between irradiating and autoclaving citrus wastes as substrate for solid‐state fermentation by Aspergillus aculeatus. (7th June 2019) - Ni, H.; Zhang, T.; Guo, X.; Hu, Y.; Xiao, A.; Jiang, Z.; Li, L.; Li, Q.
Abstract: Agricultural or food processing wastes cause serious environmental burden and economic losses. Solid‐state fermentation using these wastes is an attractive option to valorize these wastes. However, conventional autoclaving of substrate may degrade nutrients and generate toxins. Unsterilization of the substrate will cause undesired microbial contamination. Therefore, we compared irradiation with autoclaving to treat citrus wastes as substrate for solid‐state fermentation by Aspergillus aculeatus . By comparing microbial growth, enzymes tested and medium consumption, irradiated substrate had higher biomass and extracellular protein, more sugar consumption and higher enzyme production than those with autoclaved substrate. Irradiation prevented the generation of cell‐inhibiting components such as 5‐hydroxymethylfurfural (5‐HMF) whereas preserved the flavonoids well that are often enzyme inducers. These findings suggest that irradiation of agricultural and food processing wastes as substrate has advantages over autoclaving for solid‐state fermentation. Significance and Impact of the Study: This study proposes irradiation as an alternative to sterilize agricultural residues rich in nutrients and thermosensitive compounds, such as citrus wastes for fungal solid‐state fermentation and production of enzymes. Significance and Impact of the Study: This study proposes irradiation as an alternative to sterilize agricultural residues rich in nutrients and thermosensitive compounds, such as citrus wastes for fungal solid‐state fermentation and production of enzymes.